The voluntary operant and the operant nature of volition: Three views. Issue 1 (28th November 2022) - Neuringer, Allen
Abstract : Many philosophers, psychologists, and lay folk associate volition with autonomy (actions are independent of an individual's environment) and free will (individuals originate their actions). Most behaviorists hold these views to be incompatible with behavior analyses. The present paper describes volition as interpreted by B. F. Skinner, Howard Rachlin, and Allen Neuringer. Skinner relates volition to positively reinforced operant behavior. That works because, like operants, voluntary actions are free, in the sense of not physically constrained; they affect their environments, often resulting in positive outcomes, and are sometimes unpredictable. Rachlin, while incorporating Skinnerian methods, interprets volition within his own Teleological Behaviorism framework. For Rachlin, reinforcement of an individual response is often incompatible with voluntary control, thereby disagreeing with Skinner. Responses are voluntary only when they are members of extended response patterns. Neuringer also begins with Skinner's operants, but argues that, under the control of reinforcing consequences, both voluntary actions and operant responses are sometimes predictable and other times "truly" unpredictable. Neuringer does not assume that environments determine voluntary actions, thereby disagreeing with Skinner and Rachlin. Taken together, the agreements and disagreements among these three behaviorists may help to shed light on the relationship between operants and volition.